Multiple Epidermolytic Acanthomas: Rare Vulval Lesions Which May be Mistaken for Viral Warts. (January 2020) - Irwin, Steven; Karim, Afzal; McHenry, Pamela; Hutchinson, Sonya; Miller, Keith; Jamison, Jackie; Houghton, Joseph; McCluggage, W. Glenn
Abstract : Epidermolytic acanthoma is a rare benign lesion that most often presents as a solitary or multiple small papular lesions on the trunk, face, limbs or external male genitalia. Only a small number of cases have been reported occurring on the vulva and clinically and histologically they may mimic and be misdiagnosed as viral warts. We report 2 cases of multiple epidermolytic acanthomas localized to the vulva. Molecular tests ( in situ hybridization and polymerase chain reaction) showed no evidence of human papillomavirus infection and p16 staining was negative. We stress the need for pathologists to consider epidermolytic acanthoma in the differential diagnosis of multiple vulval lesions resembling viral warts.